Acute Necrotizing Fasciitis Caused by Rhizopus Infection in a Patient with Diabetes and Pulmonary Tuberculosis: A Case Report - Huang X; Qiu J; Pan L; Wang C; Tang C (Infection and Drug Resistance)
Xiaoqing Huang,1 Junke Qiu,1 Lei Pan,1 Caihong Wang,1 Chuanfeng Tang2 1Tuberculosis Intensive Care Unit, Zhejiang Hospital of Integrated Traditional Chinese and Western Medicine, Hangzhou, Zhejiang, People’s Republic of China; 2Emergency Department, Zhejiang Hospital of Integrated Traditional Chinese and Western Medicine, Hangzhou, Zhejiang, Peoples Republic of ChinaCorrespondence: Chuanfeng Tang, Emergency Department, Zhejiang Hospital of Integrated Traditional Chinese and Western Medicine, No. 208 East Huancheng Road, Hangzhou, Zhejiang, 310000, People’s Republic of China, Tel +8615155110013, Email T20237243@163.comBackground: Zygomycosis, also termed mucormycosis, is a rare yet highly fatal fungal infection caused by Mucorales species, notably Rhizopus spp.Case Presentation: This case study details a 72-year-old man with diabetes, pulmonary tuberculosis, and nephrotic syndrome who developed acute necrotizing fasciitis attributable to R. oryzae. Despite initial empirical antibiotic therapy, the infection progressed rapidly. Metagenomic next-generation sequencing (mNGS) facilitated a swift diagnosis, identifying R. oryzae in blood and drainage samples. The treatment included amphotericin B and isavuconazole, along with aggressive surgical debridement. The patient exhibited substantial improvement, and he was discharged after stabilization.Conclusion: This case highlights the critical role of early diagnosis through mNGS and the need for a multidisciplinary approach to manage severe mucormycosis in immunocompromised patients.Keywords: Rhizopus infection, acute necrotizing fasciitis, diabetes, case report